Multiple sclerosis and the risk of infection: Association of British Neurologists consensus guideline. Issue 5 (21st July 2022) - Cauchi, Marija; Willis, Mark; Andrews, Angela; Backx, Matthijs; Brownlee, Wallace; Ford, Helen L; Gran, Bruno; Jolles, Stephen; Price, Sian; Rashid, Waqar; Schmierer, Klaus; Tallantyre, Emma C
Abstract : Infection in people with multiple sclerosis (MS) is of major concern, particularly for those receiving disease-modifying therapies. This article explores the risk of infection in people with MS and provides guidance—developed by Delphi consensus by specialists involved in their management—on how to screen for, prevent and manage infection in this population.